Gut-directed hypnotherapy for functional abdominal pain or irritable bowel syndrome in children: a systematic review. Issue 4 (6th December 2012) - Rutten, Juliette M T M; Reitsma, Johannes B; Vlieger, Arine M; Benninga, Marc A
Abstract : Objectives: Gut directed hypnotherapy (HT) is shown to be effective in adult functional abdominal pain (FAP) and irritable bowel syndrome (IBS) patients. We performed a systematic review to assess efficacy of HT in paediatric FAP/IBS patients. Methods: We searched Medline, Embase, PsychINFO, Cumulative Index to Nursing and Allied Health Literature databases and Cochrane Central Register of Controlled Trials for randomised controlled trials (RCT) in children with FAP or IBS, investigating efficacy of HT on the following outcomes: abdominal pain scores, quality of life, costs and school absenteeism. Results: Three RCT comparing HT to a control treatment were included with sample sizes ranging from 22 to 52 children. We refrained from statistical pooling because of low number of studies and many differences in design and outcomes. Two studies examined HT performed by a therapist, one examined HT through self-exercises on audio CD. All trials showed statistically significantly greater improvement in abdominal pain scores among children receiving HT. One trial reported beneficial effects sustained after 1 year of follow-up. One trial reported statistically significant improvement in quality of life in the HT group. Two trials reported significant reductions in school absenteeism after HT. Conclusions: Therapeutic effects of HT seem superior to standard medical care in children with FAP or IBS. It remains difficult to quantify exact benefits. The need for more high quality research is evident.